Coordinating Ifs. (21st May 2021) - Khoo, Justin
Abstract: Accounting for the behavior of conjoined and disjoined if -clauses is not easy for standard theories of conditionals that treat if as either an operator or restrictor. In this paper, I discuss four observations about coordinated if -clauses, and motivate a semantics for conditionals that reorients the compositional structure of the restrictor theory. On my proposal, if -clauses provide restrictions on modal domains, but they do so by way of a higher type intermediary—a set of propositions—that is collapsed by the modal. I argue that combining this view with an independently plausible type-shifting operation applied to or and and predicts the range of data we find for conditionals with coordinated if -clauses.